Brain gain (drain), immigration and global network: Nepalese students in the UK 1. (25th October 2011) - Bhattarai, Keshab
Nepalese students in UK are struggling to balance tuition and other expenses in the short-run and for the gainful employment in the long run. The opportunity cost of emigration in a labour surplus economy of Nepal is very little in comparison to benefits from increased flow of remittances, transfer of knowledge, ideas and technologies. Net emigration results in brain gain rather than brain drain to Nepal and benefits in terms of output, employment and the stability in wages and inflation to the UK. Both governments, NPCCUK and NRNA can make this process more efficient by developing right mechanism and policies.